Consumer Intention of Purchasing Plant-Based Milk in Indonesia - Harold Adhitjan; Floriane Marguerite; Umar Rayendra Wahyu; Roozbeh Babolian Hendijani (Publikasi Indonesia, 2024)
In the context of achieving Sustainable Development Goals (SDGs), advancements in food technology, notably plant-based alternatives, are gaining popularity. Aligning with SDG targets such as good health and well-being (SDG 3), responsible consumption and production (SDG 12), and climate action (SDG 13), the adoption of plant-based milk signifies progress towards a sustainable food system. This study investigates the determinants influencing Indonesians' intention to purchase plant-based milk, addressing a notable research gap in developing markets. The study collected data from 300 respondents through social media, resulting in 297 valid responses. Analysis using SMARTPLS reveals that attitude, environmental concern, health consciousness, price, and subjective norms all have a significant relationship with the intention to purchase plant-based milk, with attitude and environment identified as the strongest drivers. These findings have practical implications for plant-based milk business managers and other stakeholders interested in improving their competitiveness while contributing to a more sustainable environment.